The effect of exercise modality on respiratory muscle performance in triathletes - Boussana, A.; Matecki, S.; Galy, O.; Hue, O.; Ramonatxo, M.; Le Gallais, D. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The aim of this study was to examine the effects of the cycle-run and run-cycle successions of the triathlon and duathlon, respectively, on respiratory muscle strength and endurance. Methods: Respiratory muscle strength was assessed by measuring maximal inspiratory (PImax) and expiratory (PEmax) pressures. Respiratory muscle endurance was assessed by measuring the time limit (Tlim). Twelve triathletes participated in a three-trial protocol. The first trial consisted of an incremental cycle test to assess the maximal oxygen uptake (&OV0312O2max) of triathletes. Trial 2 consisted of 20 min of cycling followed by 20 min of running (C-R), and trial 3 consisted of 20 min of running followed by 20 min of cycling (R-C). Trials 2 and 3 were performed at the same metabolic intensity (% &OV0312O2max). PImax and PEmax were measured before and 10 min after C-R and R-C, and 1 min after the post-C-R and post-R-C Tlim measurements (PImax 1'). Tlim was measured 1 d before and 30 min after C-R and R-C. Results: The results showed a significant decrease in PImax after C-R (126.7 +/- 4.3 cmH2O, P < 0.05) and R-C (123.7 +/- 4.9 cmH2O, P < 0.05) compared with the baseline values (130 +/- 3.8 and 129.6 +/- 4.3 cmH2O, respectively). PImax 1' showed a significantly greater decrease after R-C versus C-R (111.2 +/- 5.5 cmH2O vs 121.2 +/- 3.9 cmH2O, respectively, P < 0.001). Tlim after C-R (3.3 +/- 0.3 min) and R-C (2.1 +/- 0.3 min) decreased significantly compared with baseline values (4.19 +/- 0.3 min and 4.02 +/- 0.3 min, respectively). However, the Tlim decrease after R-C was significantly greater than after C-R (P < 0.001). Conclusion: We concluded that respiratory muscle strength and endurance were less decreased after the cycle-run succession and that cycling induced a greater decrease in respiratory muscle endurance than running.